Electroanalytical Performance of a Freestanding Three‐Dimensional Graphene Foam Electrode. Issue 1 (5th December 2013) - Figueiredo‐Filho, Luiz C. S.; Brownson, Dale A. C.; Fatibello‐Filho, Orlando; Banks, Craig E.
Abstract The electroanalytical performance of a freestanding three‐dimensional (3D) quasi‐graphene macrostructure is evaluated and benchmarked towards model analytes in aqueous solutions. Due to the freestanding 3D graphene foam exhibiting near‐super‐hydrophobicity and consequently giving rise to poor voltammetric signatures in aqueous solutions (Brownson et al., J. Mater. Chem. A, 2013, 1, 5962), we explore a 'washing' pretreatment procedure to reduce the hydrophobic behaviour of the 3D graphene macrostructure in order to try and allow its effective application in such cases. Herein, the electrochemical properties and resultant electroanalytical performance of the pretreated 3D graphene foam (3D‐GF) is critically explored and compared to a freestanding 3D reticulated vitreous carbon (3D‐RVC) foam alternative towards the sensing of a range of important analytes via cyclic voltammetry in aqueous solutions; namely, uric acid (UA), acetaminophen (AP) and dopamine hydrochloride (DA). It is found that the 3D‐RVC exhibits improved electroanalytical characteristics with larger linear ranges and lower limit of detections achievable over that of the 3D‐GF towards the target analytes. This work provides a vital insight into electroanalysis using 3D graphene and carbon foams.